Cervical in-transit metastasis from a truncal basal cell carcinoma. (22nd July 2010) - Khan, Muhammad Kamaal; Powell, Steven; Cox, Neil; Robson, Andrew; Murrant, Nick
Abstract : The authors describe a rare case in which a cervical metastatic basal cell carcinoma (BCC) occurred from a small, non-ulcerated primary lesion on the trunk of a female patient. The metastasis had the same immunohistochemical staining pattern as several biopsies from the primary site. It was immediately adjacent to the left neck regional nodes and we view this as an in-transit metastasis. There is often debate about the validity of BCC metastases to lymph nodes but an in-transit lesion strengthens the argument that this does rarely occur.